Cervical Epidural Spinal Analgesia for Acute Management of Severe Unilateral Forelimb Lameness: Case Report - Amanda R. Watkins (Frontiers Media S.A., 2021)
A 20-year-old Quarter Horse gelding was presented with severe right forelimb lameness (5/5 AAEP Lameness Scale) due to a tear of the superficial digital flexor muscle which was diagnosed via palpation of swelling and ultrasonography revealing major muscle fiber disruption and hematoma formation. When traditional systemic therapy (non-Steroidal anti-inflammatories) did not restore clinically acceptable comfort and the risk of supporting limb laminitis became a reasonable concern, a cervical epidural catheter was placed between the first and second cervical vertebrae in the standing, sedated patient using ultrasound guidance. The gelding was treated with epidural morphine (0.1 mg/kg every 24 h then decreased to 0.05 mg/kg every 12 h) and was pain-scored serially following treatment. Spinal analgesia was provided for 3 days. Pain scores significantly decreased following each treatment with morphine, and the gelding was successfully managed through the acutely painful period without any adverse effects associated with the C1-C2 epidural catheter placement technique, the epidural morphine, or contralateral limb laminitis. At the 2-month follow-up, the gelding was walking sound with no complications seen at the catheter insertion site. In this case, spinal analgesia using epidural morphine administered via a cervical epidural catheter was an effective and technically achievable option for pain management associated with severe forelimb muscle injury in a horse.